Prospects of Using the Augmented Reality for Training Foreign Students at the Preparatory Departments of Universities in Ukraine (Pedagogy of Higher and Secondary Education, 2018)
Zinonos N.O., Vikhrova O.V., Pikilnyak A.V. Prospects of Using the Augmented Reality for Training Foreign Students at the Preparatory Departments of Universities in Ukraine.The purpose of the study is to highlight the potential and the prospects of using the augmented reality in the mathematical education for foreign students at the preparatory departments of universities. Objectives of the study: to determine the peculiarities of the virtualization of the training of foreign students at the preparatory departments of universities, as well as the possibilities of using the technology of complementary reality in the teaching of mathematics. Object of research: a virtually oriented educational environment of foreign students at the preparatory departments of universities. Subject of research: virtualization of learning with the augmented reality of mathematical education of foreign students at the preparatory departments of universities. Used research methods: theoretical — analysis of scientific and methodological literature; empirical-study, observation of the educational process. Results of the research: on the basis of the analysis of scientific publications, the notion of virtualization of education and the virtually oriented educational environment of foreign students at the preparatory departments of higher educational institutions is described. The main conclusions and recommendations: 1) the article outlines the possibilities and prospects of using the augmented reality in the mathematical education for foreign students at the preparatory departments of universities; 2) the considering the various targets of mobileapplications, which are used in solving mathematical problems, as well as analysis of the characteristics of various practical achievements of using the augmented reality in the mathematical preparation for foreign students at the preparatory departments of universities, it is planned to devote a separate work.
Keywords: foreign students; augmented reality; a virtually oriented learning environment; mathematics training